PENAMBAHAN SINBIOTIK (Lactobacillus dan Ekstrak Ubi Jalar) UNTUK MENINGKATKAN KESEHATAN BENIH IKAN NILA (Oreochromis niloticus) : indonesia - happy, happymarlini; Oktaviana, Adni; Febriani, Dian (Jurnal Perikanan Terapan, 2022)
Tilapia is an important part of freshwater aquaculture in Indonesia. This fish has a high survivability and tolerance for poor water quality and has become a leading commodity for freshwater aquaculture in several Southeast Asian countries including Indonesia. Probiotics are food additives in the form of live microbes that have a beneficial effect on the host by increasing the balance of microbes in the digestive tract. Tilapia rearing was using a cement pond 4x3 meters with a total of 2 pools. Preparation of the container begins with installing the tarpaulin. After that, clean or rinse the pool. Then the pond is filled with water as high as 30 cm from the beginning of maintenance to harvest and left for 1-2 days. Ponds are aerated to increase oxygen levels in the water. Maintenance was carried out for 30 days until the size was 6-8 cm, with commercial feeding in the form of pf800 which had been mixed with synbiotics. From the results of tilapia rearing, it was concluded that the addition of synbiotics in the feed to improve the health of tilapia seeds during 30 days of maintenance was normal. The addition of sweet potato extract and lactobacillus as probiotics is good for fish health.